An Evaluation on Theoretical Foundations of Space and Place Concepts in Modern Geographical - Selim Bozdoğan; Sedat Benek (Coğrafya Dergisi)
The purpose of this study is to examine how the concepts of space and place are theorized in the history of thought and their effects on geographical thought. Place and space are occasionally used interchangeably and sometimes have completely different definitions in today’s dictionaries, both in ordinary and discipline dictionaries. There are different ways of defining the concepts of space and place in the discipline of geography. Therefore, in order to understand the different definitions of space and place in geography, it is essential to analyze the epistemological traditions that feed on the ways of using both concepts. As it is a conceptual, historical, and theoretical study, “textual analysis” technique, which is a qualitative method, has been used. In conclusion, this research looks at how two different perspectives on space and place affect geographical thinking. The first is modern thought’s evolving notion of “absolute space.” The second concern is phenomenologists’ challenges of the concept of absolute space. Space and location are treated independently in different philosophical systems. The critique of the phenomenological dimension of both absolute space and place approaches is put forward, in general terms, based on the concept of social space. In this context, David Harvey and Doreen Massey highlight the relational dimension of space and place based on the idea of social space. In this relation, space as a social product expresses the sum of places. It is a phenomenon that has been ignored for a long time that places make sense of space as a “difference/total.”